Perceptual and Structural Facilitators and Barriers to Becoming a Surgeon: A Qualitative Study of African American and Latino Surgeons. (September 2018) - Ulloa, Jesus G.; Viramontes, Omar; Ryan, Gery; Wells, Kenneth; Maggard-Gibbons, Melinda; Moreno, Gerardo
Abstract : Purpose: As racial and ethnic heterogeneity in the United States increases, it is important that the health care workforce, including surgery, mirror that diversity. Structural and perceptual barriers may contribute to an underrepresentation of African American and Latino surgeons. Understanding these barriers may translate into interventions and, in turn, improved diversification of the U.S. surgery workforce. Method: In 2016, the authors conducted in-depth semistructured interviews, exploring structural and perceptual barriers that African American and Latino surgeons face. The authors used conventional qualitative techniques to analyze data and identify themes. Results: The authors interviewed 23 participants and observed three major themes characterizing the path to becoming a surgeon: creating a path to medicine, surgical culture, and mentorship. Subthemes provided further nuance. For creating a path to medicine, the subthemes were personal attributes, family support, community assets/barriers, and minority experience. For surgical culture, the subthemes comprised quality of life, surgeon–patient relationship, and restoring health. For mentorship, the subthemes were aspirational figures, formal programs/peer support, and professional opportunities. Experiences described by African Americans and Latinos were similar, but the experiences of participants of different self-identified childhood socioeconomic status were dissimilar. Conclusions: The path to a surgical career as experienced by African American and Latino surgeons is heavily influenced by mentors mediating their integration into surgical culture and engendering a feeling of belonging. Future surgeons from groups underrepresented in medicine would benefit from identifying aspirational figures early, a structured introduction into the rigors of the profession, and a deconstruction of negative surgical norms.